Increased serum levels of lipopolysaccharide and antiflagellin antibodies in patients with diarrhea‐predominant irritable bowel syndrome. Issue 12 (21st September 2015) - Dlugosz, A.; Nowak, P.; D'Amato, M.; Mohammadian Kermani, G.; Nyström, J.; Abdurahman, S.; Lindberg, G.
Abstract: Background: Innate immune responses to conserved microbial products such as lipopolysaccharide (LPS) and flagellin are likely important in microbial–host interactions and intestinal homeostasis. We hypothesized that bacterial translocation and activation of mucosal immunity against common microbial antigens might be involved in the development of irritable bowel syndrome (IBS). We therefore compared serum levels of LPS, soluble CD14 (sCD14), and flagellin antibodies between patients with different subtypes of IBS and healthy controls. Methods: We analyzed serum obtained from 88 patients (74 females) aged 19(43)–73 years and 106 healthy volunteers (77 females) aged 19(38)–62 years. Diarrhea‐predominant IBS (D‐IBS) was present in 32 patients (36%), 23 patients (26%) had constipation‐predominant IBS (C‐IBS), and 33 patients (38%) had A‐IBS. We used ELISA for sCD14 and antiflagellin immunoglobulin G and limulus amebocyte assay for LPS. Abdominal symptoms and psychiatric comorbidities were assessed using validated questionnaires. Key Results: We found a significantly higher serum level of LPS in patients with D‐IBS compared to controls ( p = 0.0155). The level of antibodies to flagellin was higher in patients with IBS than in controls (mainly driven by higher levels in D‐IBS, p = 0.0018). The levels of sCD14 were lower in D‐IBS patients compared to controls ( p = 0.0498). We found a weak, but significant correlation between the levels of antiflagellin antibodies and anxiety among IBS patients ( ρ = 0.38; p = 0.0045). Conclusions & Inferences: Our results support the concept that immune reactivity to luminal antigens may have a role in the development of D‐IBS. The serum level of antiflagellin antibodies was found to correlate with patients' self‐reported anxiety score. Abstract : Immune reactivity to luminal antigens may have a role in the development of D‐IBS. We compared serum levels of LPS, soluble CD14 (sCD14), and flagellin antibodies between 88 patients with different subtypes of IBS and 106 healthy controls. We used ELISA for sCD14 and antiflagellin IgG and limulus amebocyte assay for LPS. Patients with D‐IBS have higher serum levels of LPS and antibodies to flagellin, but lower levels of sCD14 compared to controls. The serum level of antiflagellin antibodies was found to correlate with patients' self‐reported anxiety score.